'I was thinking too much': experiences of HIV‐positive adults with common mental disorders and poor adherence to antiretroviral therapy in Zimbabwe. Issue 7 (23rd March 2015) - Kidia, Khameer; Machando, Debra; Bere, Tarisai; Macpherson, Kirsty; Nyamayaro, Primrose; Potter, Lucy; Makadzange, Tariro; Munjoma, Ronald; Marufu, Marshall; Araya, Ricardo; Safren, Steven; O'Cleirigh, Conall; et al.
Abstract Objective To document the lived experiences of people with both poor mental health and suboptimal adherence to antiretroviral therapy in high HIV prevalence settings. Methods In‐depth qualitative interviews were conducted with 47 (female = 31) HIV‐positive adults who scored above the cut‐point on a locally validated scale for common mental disorders (CMDs). Purposive sampling was used to recruit participants with evidence of poor adherence. Six additional key informant interviews (female = 6) were conducted with healthcare workers. Data were collected and analysed inductively by an interdisciplinary coding team. Results The major challenges faced by participants were stressors (poverty, stigma, marital problems) and symptoms of CMDs ('thinking too much', changes to appetite and sleep, 'burdened heart' and low energy levels). Thinking too much, which appears closely related to rumination, was the symptom with the greatest negative impact on adherence to antiretroviral therapy among HIV‐positive adults with CMDs. In turn, thinking too much was commonly triggered by the stressors faced by people living with HIV/AIDS, especially poverty. Finally, participants desired private counselling, access to income‐generating activities and family engagement in mental health care. Conclusions Better understanding of the local expression of mental disorders and of underlying stressors can inform the development of culturally sensitive interventions to reduce CMDs and poor adherence to antiretroviral therapy.